L’anima vegetale del pensiero (Materiali di Estetica. Terza serie, 2019)
This article presents and discusses some theses elaborated by Emanuele Coccia in his recent book The life of Plants. A theme that seemed abandoned to the margins of philosophical conceptuality, the idea of nature, and in particular the idea of plant life, seems to have acquired a renewed interest by philosophers in recent times. Starting from the radical rethinking of some metaphysical categories (subject, object, immersion, life, form), the article discusses the possibility of giving back to the philosophy of nature the importance it deserves. As the book, the article closes with a reflection on the role of philosophy in the future university.